d^2y/dx^2+9y=3+sin (3x)
"Solution:~This ~is~ second~ order~ linear~ non-homogeneous ~differential ~\\\\ equation~ with ~ constant ~ coefficient ~which ~is ~in ~the ~form~ay''+by'+cy=g(x)"
"\\therefore Substitute \\frac{d^2y}{dx^2 }=y''\n\\\\ \\therefore ~the ~given ~differential ~equation~ is ~written ~as~y''+9y=3+sin(3x)"
"General ~ Solution~ to ~a(x)y''+ b(x)y'+ c(x)y=g(x)~can ~be ~written ~ as~ \\\\y=y_h +y_p ............................................................................................(1)\n\\\\Where~ y_h ~is~ the ~solution~ to~ the~ homogenous ~ODE ~a(x)y''+ b(x)y'+ c(x)y=0\n\\\\and~y_p~particular ~solution, is ~any~ function~ that ~satisfies~the ~\\\\non-homogenous~equation"
"Now, we ~find, y_h~ and~ y_p ."
"To ~find~ y_h: We~know ~that~, the~ general~ solution~ of~ y''+k^2y=0~is~ \\\\y=c_1~cos(kx)+c_2~sin(kx)\n\\\\\\therefore The ~general ~ solution ~ of~ y''+9y=0~\\Rightarrow y''+3^2y=0~is~ ~\n\\\\y=c_1~cos(3x)+c_2~sin(3x)\n\\\\\\therefore y_h=c_1~cos(3x)+c_2~sin(3x).............................................................(2)"
"To ~ find~y_p:~Find ~y_p~that~satisfies~y''+9y=3+sin(3x)\\\\\\Rightarrow y=\\frac{1}{3}-\\frac{x~cos(3x)}{6}\n\\\\ \\therefore y_p=\\frac{1}{3}-\\frac{x~cos(3x)}{6}........................................................................(3)"
"\\therefore The~ general ~ solution~ y=y_h+y_p~ is~\n\\\\y=c_1~cos(3x)+c_2~sin(3x)+\\frac{1}{3}-\\frac{x~cos(3x)}{6}"
Comments
Leave a comment